PENGETAHUAN MASYARAKAT TENTANG TRANSPLANTASI KARANG BERBASIS FISHDOM DI PULAU TUNDA, BANTEN SEBAGAI DASAR PROGRAM KREATIVITAS MAHASISWA PENGABDIAN PADA MASYARAKAT - Sri Fajriah; Nada Thalia Permata Adriani; Muhamad Iqbal Muttaqin; Edo Ahmad Solahudin; Ahmad Luthfi Nur Fauzi; Weksi Budiaji; Muh. Herjayanto; Syifa Alfiah; Nur ‘Aida (Universitas Mataram, 2023)
Coral rehabilitation on Tunda Island is carried out to support marine tourism, which is the mainstay of the community tourism sector. Because of this, the Student Creativity Program (PKM) is being carried out, namely community service (PM) related to fishdom-based coral transplants. This activity is the creation of artificial coral reefs that aim to restore underwater ecosystems, fish populations and diversity. The program's success starts from selecting locations and community participation through community knowledge. Based on this, the activity objectives were to obtain information on community knowledge about coral and marine ecotourism, recommendations for implementing coral transplants, and the location of PKM-PM on Tunda Island. The stages of the activity are planning, data collection in the community, and data analysis. Coordination is carried out with the local government and tourism awareness groups (Pokdarwis). The data was collected through non-formal interviews with community representatives in 2 RW 6 RT in Wargasara Village, Tunda Island. The interviews showed that more than 50% of the people of Tunda Island had good knowledge about coral reefs and their functions, coral transplants, the condition of coral reefs, fish locations and ecotourism on Tunda Island. More than 60% of the people of Tunda Island do not know the structure of the fishdom and have never attended socialization and training on coral transplantation. Therefore, the community suggests conducting coral transplantation training and fishdom construction on Tunda Island is necessary. The community suggested that coral transplants could be carried out in East Tanjungan and fishdom placement on the North Beach to support underwater tourism on Tunda Island. Community involvement, especially Pokdarwis, can guarantee the sustainability of PKM-PM activities on Tunda Island through coral conservation education-based tours.